Ecological study and coral mortality in the horizontal marine zone of Beras Basah Island, Bontang - Rosdiani, Yulistika; Yulianda, Fredinan; Damar, Ario (Acta Aquatica: Aquatic Sciences Journal, 2025)
This study aims to assess the ecological value and coral mortality in the horizontal marine zone of Beras Basah Island. The research was conducted by observing coral reefs at four stations positioned horizontally at depths of 3 meters and 5 meters using the Line Intercept Transect (LIT) method. The key parameters analyzed in this study included coral cover percentage, diversity index, dominance index, evenness index, and mortality index. The recorded coral cover percentages were as follows: hard coral (26.91%), soft coral (16.42%), sponge (0.47%), other biotic components (0.44%), algae (5.86%), dead coral with algae (21.07%), dead coral (1.78%), sand (6.60%), rubble (9.26%), and silt (11.19%). The condition of coral reefs in the horizontal marine zone of Beras Basah Island was classified as moderate, with a live coral cover value of 26.91%, based on the classification by Gomez and Yap (1988). The highest diversity index value (2.46) was recorded at Station 1(a), indicating a relatively stable community structure, while the lowest diversity index value (1.98) was observed at Station 3(b), reflecting lower diversity and potential environmental stress or disturbance in the area. This is further supported by the highest dominance index value (0.17) also found at Station 3(b). The highest evenness index values (0.87) were observed at Stations 1(a) and 1(b), indicating stable communities with high similarity and evenness. The highest coral mortality index (0.53) was recorded at Station 2(a), located in the northern area at a depth of 3 meters in the waters of Beras Basah Island. Keywords: Beras Basah Island; Biodiversity; Coral Reef; Ecological Index; LIT Method; Mortality Index